2016
DOI: 10.1136/bmjopen-2016-012222
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of AA CRASH: a prospective observational study evaluating the incidence and pathogenesis of adverse post-traumatic sequelae in African-Americans experiencing motor vehicle collision

Abstract: IntroductionA motor vehicle collision (MVC) is one of the most common life-threatening events experienced by individuals living in the USA. While most individuals recover following MVC, a significant proportion of individuals develop adverse post-traumatic sequelae such as post-traumatic stress disorder or persistent musculoskeletal pain. Adverse post-traumatic sequelae are common, morbid and costly public health problems in the USA and other industrialised countries. The pathogenesis of these disorders follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Details of the original study methods have been previously published. 2, 22, 23 In brief, participants were screened and enrolled by trained research assistants. Screening occurred during day and evening hours based on availability of research assistants and occurred for approximately 12 to 16 hours each day at each site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the original study methods have been previously published. 2, 22, 23 In brief, participants were screened and enrolled by trained research assistants. Screening occurred during day and evening hours based on availability of research assistants and occurred for approximately 12 to 16 hours each day at each site.…”
Section: Methodsmentioning
confidence: 99%
“…Screening occurred during day and evening hours based on availability of research assistants and occurred for approximately 12 to 16 hours each day at each site. 22, 23 Data were collected by trained research assistants during the ED visit using patient interview; additional data were collected from the medical record following the completion of the ED visit.…”
Section: Methodsmentioning
confidence: 99%
“…Participants. Participants were enrolled as part of two large, multicenter prospective cohorts of adult patients (one of European-Americans and one of African-Americans) that recruited from eight EDs as previously described [23]. The study was approved by the IRB at each of the study sites, and all participants provided written informed consent.…”
Section: Tryumph Research Network Cohortmentioning
confidence: 99%
“…Baseline characteristics of participants in the discovery and replication cohorts are shown in Table 1 . The motor vehicle collision (MVC) cohort has been described previously ( 49 ). This study exclusively enrolled African American women and men ( n = 930) who reported to the emergency department (ED) within 24 h of an MVC.…”
Section: Resultsmentioning
confidence: 99%
“…This prospective longitudinal study enrolled African American individuals ≥18 and ≤65 years of age presenting to the ED within 24 h of MVC. The details of this study have been described previously ( 49 ). This study was approved by the institutional review boards at the data-coordinating center (The University of North Carolina at Chapel Hill) and at all participating hospitals.…”
Section: Methodsmentioning
confidence: 99%